Социальное здоровье обучающихся в гетерогенной образовательной организации - Байкова, Лариса Анатольевна (International Dialogues on Education Journal, 2016)
In the article the idea of social health and criteria for social wellness among children of diverse age groups are discussed. The results of research on the topic of social health and special needs of children from heterogeneous educational institutions are shown. The educational needs of children from heterogeneous groups are largely similar to each other – they all strive for self-fulfilment through high-quality education, they all need creative outlets and a broad social circle. One third of those children are in need of close pedagogical and psychological support. Monitoring the characteristics of their dominant social orientation, social and psychological adaptation, self-actualization and specific educational needs will allow us to apply an individual and differential approach in organizing psychological and pedagogical support for students’ social health.